SAT0233 A randomised comparison of care provided by a clinical nurse specialist, inpatient team care and day patient team care in rheumatoid arthritis (ra). (1st June 2001) - Tijhuis, GJ; Zwinderman, AH; Hazes, JM; Van den Hout, WB; Breedveld, FC; Vlieland, TP Vliet
Abstract : Background: The role of clinical nurse specialists in the management of patients with RA is evolving, and their effectiveness in comparison with care provided by a rheumatologist alone has been established. However, controlled studies showing how the effectiveness of clinical nurse specialists compares to that of multi-disciplinary team care, a treatment strategy that is considered to be optimal in chronic disease management, are lacking. Objectives: The first aim of the study was to compare the clinical effectiveness of care delivered by a clinical nurse specialist with inpatient team care and day patient team care in patients with RA. The second aim was to determine factors predicting clinical response. Methods: A multi-centre, randomised controlled clinical trial including consecutive outpatients with RA and progressive functional limitations over the past 6 weeks. Clinical assessments recorded on study entry, weeks 6, 12, 26 and 52 comprised the HAQ, MACTAR functional index, RAND-36 quality of life questionnaire, health utility rating scale (RS) and DAS. Patients? satisfaction with care was measured on a visual analogue scale. Within-group differences between baseline and follow-up scores were tested with the Wilcoxon signed rank matched-pairs test. Co-variance analysis was used to analyse between-group differences and to determine factors predicting clinical response. Results: 210 patients (median age 58 years, median disease duration 1.8 years and median HAQ score 1.25) were included in the study. Within all 3 groups functional status, quality of life, health utility and disease activity improved significantly over time (all P-values <0.05). A comparison of clinical outcome among the three groups and a comparison between the nurse specialist group and the inpatient and day patient care groups together did not show any sustained significant differences. Subgroup analysis showed that with increasing age, the most favourable outcome according to the HAQ shifted from care provided by a clinical nurse specialist and inpatient care to day patient care. Patients? satisfaction with care was significantly lower in the nurse specialist group than in the inpatient and day patient care groups (P < 0.001). Conclusion: Care provided by a clinical nurse specialist appears to have a similar clinical outcome in comparison with inpatient and day patient team care in patients with RA. Age was the only factor related to differences in functional outcome between the three treatment groups. The choice of management strategy may, apart from age, further be dependent on the availability of facilities, the preferences of patients and health care providers and on economic considerations.